What predicts teachers' use of digital learning in Germany? Examining the obstacles and conditions of digital learning in special education. Issue 1 (1st January 2021) - Börnert-Ringleb, Moritz; Casale, Gino; Hillenbrand, Clemens
ABSTRACT: The school closures during the COVID-19 outbreak triggered ashift towards digital learning. Whilst this is amajor challenge for mainstream education, the implementation of digital learning poses an even bigger challenge for special education teachers, as they are confronted with different learning requirements which might hinder digital learning processes. Previous research identified obstacles to digital learning in mainstream education, but conditions of digital learning in special education remain unclear. This article aims to provide insights on conditions of digital learning in special education at teacher-, school-, and student-levels. We examined whether the intention to use digital learning in special education is predicted by (1) teachers' self-efficacy,  attitudes and their perceived usability of digital learning, (2) perceived organisational support and (3) perceived obstacles on student-level. Data of N = 722 special education teachers were collected during the pandemic. Results of mixed models indicate that specific self-efficacy in digital learning and perceived support were the strongest predictors for the intention to use digital learning, while alack of students' self-regulation and parental support represented major obstacles. The results underline the need for specific training in digital learning for special education teachers, and interventions in digital learning for students with special needs.